2014
DOI: 10.1037/h0099375
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious posttraumatic growth: Predictors of growth and relationships with adjustment.

Abstract: Posttraumatic growth (PTG) is now recognized as a possible outcome in the wake of trauma that has been experienced either directly or indirectly. With this in mind, the aims of the current study were threefold: to assess the applicability of Calhoun and Tedeschi’s (2006, 1996) five-factor model of PTG in relation to vicarious PTG; assess the factors that are predictive of vicarious PTG; and assess the extent to which vicarious PTG is able to predict adjustment. The sample comprised of 126 university students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 51 publications
1
32
0
1
Order By: Relevance
“…Cohen and Collens ( 2013 ) indicate that higher occupational load promotes the occurrence of VPTG. These positive links between occupational load and SPTG are confirmed by research related primarily to therapists (Abel et al, 2014 ; Arnold et al, 2005 ; Brockhouse et al, 2011 ; Cohen & Collens, 2013 ; Froman, 2014 ). Positive though weak associations among years of practice and VPTG were found in labour and delivery nurses (Beck et al, 2016 ).…”
Section: Occupational Loadmentioning
confidence: 74%
See 1 more Smart Citation
“…Cohen and Collens ( 2013 ) indicate that higher occupational load promotes the occurrence of VPTG. These positive links between occupational load and SPTG are confirmed by research related primarily to therapists (Abel et al, 2014 ; Arnold et al, 2005 ; Brockhouse et al, 2011 ; Cohen & Collens, 2013 ; Froman, 2014 ). Positive though weak associations among years of practice and VPTG were found in labour and delivery nurses (Beck et al, 2016 ).…”
Section: Occupational Loadmentioning
confidence: 74%
“…On the other hand, working with trauma victims may be a source of positive posttraumatic changes, which are referred to as secondary posttraumatic growth (SPTG) or vicarious posttraumatic growth (VPTG). VPTG is defined as the personal growth and meaning gained through another’s trauma (Abel, Walker, Samios, & Morozow, 2014 ). Just as in the case of posttraumatic growth (PTG) experienced by the victims of trauma, those positive changes appearing as a result of vicarious trauma relate to the perception of oneself, the relations with others, and one’s life philosophy (Arnold, Calhoun, Tedeschi, & Cann, 2005 ; Brockhouse, Msetfi, Cohen, & Joseph, 2011 ; Calhoun & Tedeschi, 2013 ; Manning-Jones, de Terte, & Stephens, 2015 , 2016 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a qualitative study by McCormack, Hagger, and Joseph (2011), the partners of Vietnam veterans shared how secondary exposure to their partners’ combat trauma led to increased empathy and marital satisfaction. More recently, a quantitative investigation by Abel, Walker, Samios, Morozow, and Bride (2014), indicated that secondary exposure among college students was positively related with VPTG. The racial and ethnic homogeneity of the samples on both studies (White Europeans), highlight the need to research VPTG in diverse cultures.…”
Section: Secondary Exposure and Vicarious Growthmentioning
confidence: 99%
“…For example, besides providing support, family and friends can also help the individual experiencing secondary exposure gain perspective or correct irrational thoughts associated with the natural disaster. Finding positive meaning in the disaster (Abel et al, 2014) and receiving support from family and friends (Manning-Jones et al, 2016) have been inversely associated with secondary traumatic stress and positively correlated with VPTG.…”
Section: The Role Of Coping and Predisaster Stressors On Secondary Stmentioning
confidence: 99%
“…Praca z ofiarami traumy może być także źródłem występowania pozytywnych zmian potraumatycznych, ujmowanych w postaci wtórnego/zastępczego wzrostu po traumie (SPTG/VPTG, secondary/vicarious posttraumatic growth), który definiuje się jako zespół pozytywnych zmian mogących wystąpić u osób niosących pomoc -dzięki traumie doświadczonej przez ich podopiecznych [6,7]. Te pozytywne zmiany występujące w wyniku zastępczej traumatyzacji, podobnie jak w przypadku potraumatycznego wzrostu (PTG, posttraumatic growth) doświadczanego bezpośrednio, odnoszą się do percepcji siebie, relacji z innymi i filozofii życiowej [6,[8][9][10].…”
Section: Wstęp Wtórny Stres I Wzrost Wśród Personelu Medycznegounclassified